DETERMINING OPTIMAL SIZE, POSITION AND COVERING MATERIAL FOR A BUSHING SHIELD - Adnan Glotiđ; Peter Kitak; Jože Pihler; Igor Tičar (Journal of Energy Technology, 2024)
This paper deals with the design optimization of insulating elements-bushings. The principle of the shield size and its position as well as the insulating material determination, based on an optimization processis presentedon the example of a bushing. The aimoftheoptimizationwas to a chieve lowest electrical fields treng thvaluesaroundabushingand the lowe stratio of the electrical fields trengthvaluesat the border of twodifferentdi electric materials; the bushings body and the dielectri clayer  that covers a shield. High electrical field streng thvaluesareone amongfactors, which can dramaticallyde crease the in sulators’ operational reliability; there fore the optimal design of a bushing with lowest electrical field strength values is desirable. An optimization procedure was carried out using Differential Evolution (DE) Algorithm combinedwith the solver of the software tool EleFAnT for solving a parametrically -written model of a bushing. EleFAnTisbasedon finite element method (FEM) with a preͲ processo rthat was made in the MATLAB soft ware tool.